THE IMPACT OF MOTIVATION ON LEARNING ENGLISH - DO’LANOVA NODIRA SHAMSIDDIN QIZI (Ta’lim innovatsiyasi va integratsiyasi, 2026)
Motivation is widely recognized as one of the most influential factors in second and foreign language acquisition. In the context of learning English as a foreign language (EFL), learners’ motivation plays a crucial role in determining their level of engagement, persistence, and overall achievement. This article examines the concept of motivation, its types, and its impact on learning English. The study analyzes intrinsic and extrinsic motivation, explores motivational factors affecting English learners, and discusses the role of teachers in enhancing learner motivation. The findings suggest that motivated learners demonstrate higher achievement, stronger language skills, and greater confidence in using English. The article also provides pedagogical implications for English language teachers.